Immuntherapie gegen Gliome: Leitthema - Sahm, Katharina; Weiss, Tobias (Der Nervenarzt, 2024)
Background Gliomas represent the most frequent malignant primary brain tumors in adults. Despite multimodal treatment concepts involving surgery, irradiation and chemotherapy, the prognosis remains poor and they are incurable. Recent insights into the interactions between the immune system and the central nervous system as well as breakthroughs in the results of other cancer types have led to the fact that various immunotherapeutic approaches against gliomas have also been investigated and in some cases specifically developed. Objective This article provides an overview of the current status of different immunotherapeutic concepts against gliomas, highlighting the advantages, disadvantages, and challenges. Additionally, it provides an overview of currently ongoing immunotherapeutic clinical trials in Germany and neighboring countries. Results Previous randomized studies on antibodies against programmed cell death protein 1 (anti-PD1) immune checkpoint inhibition, viral treatment and peptide vaccination targeting the variant III of the epidermal growth factor receptor (EGFRvIII) in glioblastomas were negative with respect to survival benefits. Conversely, other immunotherapeutic approaches, such as multivalent or driver mutation-based vaccinations, cytokine-based therapy and cell therapy, demonstrated a robust scientific foundation, with at least early studies showing promising safety and pharmacodynamic effects on the tumors. Discussion Currently, immunotherapies against gliomas should only be applied within the framework of well-designed clinical studies. There are still many knowledge gaps regarding the mechanisms of action and resistance of various immunotherapies. Accompanying translational research is essential to address these gaps and develop more effective therapies.